Kebijakan Peningkatan Pnbp dalam Pelayanan Publik di Bidang Keimigrasian - Raden Natanegara Kartika Purnama; Muhammad Arief Adillah; Cahyoko Edi Tando (Law and Human Rights Research and Development Agency, 2023)
One of the non-tax revenues in Indonesia is generated by services at Immigration Sector which is currently showing significant changes and activities. Public services provided to all citizens must be excellent and in line with the needs of the community itself. This study used a Systematic Literature Review (SLR) with PRISMA Method which also searched for articles using Scopus and ScienceDirect database because those have good reputable nationally and internationally by academics. The study resulted in 2 (two) policies in Immigration through analysis of the results of the search for the article. The first is to improve developing immigration services and the latest innovations from digital Immigration and to promote a humanist approach and accountability for its services and ease of access given. Moreover, monopoly on human resources at Immigration is currently carried out in vital cooperation due to national security and state policy especially related to intelligence analysis. Meanwhile, cooperation with other parties is limited to providing space, education in terms of increasing human resources, and cooperation to exchange information with certain parties. The conclusion of this study led to 2 research results, which are policies to improve services and policies to strengthen immigration. The suggestions for future research are in-depth field research using qualitative or quantitative method on immigration agencies and other contributive factors to state revenue.